National Innovation and the Role of the College Sector - Belanger, Charles H.; Mount, Joan; Madgett, Paul; Filion, Ivan (Canadian Journal of Higher Education, 2005)
This paper discusses the role of the colleges in applied research in the context of Canada's capability for innovation in a globally competitive arena. The analysis focuses upon issues around an expanded mandate related to applied research. To explore the state of readiness of the college sector, it draws upon the results of a survey distributed to 150 college and institute presidents in Canada, as well as upon other recent studies. The discussion ends with suggested policy avenues to maximize the effectiveness of this sector's contribution to the nation's innovation agenda.